1981
DOI: 10.1088/0022-3727/14/8/008
|View full text |Cite
|
Sign up to set email alerts
|

Double layer formation in a magnetised laboratory plasma

Abstract: Double layers in a current-carrying magnetised argon plasma are studied experimentally. The layer evolves from an unstable anode sheath when the anode voltage has reached a critical value which depends on the neutral gas pressure. The double layer is an oscillating, three-dimensional structure enclosing both axially and radially a plasma at higher potential which is maintained by a low rate of ionisation due to the accelerated electrons. Axially accelerated electrons and radially accelerated ions have been det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

1986
1986
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(17 citation statements)
references
References 10 publications
1
16
0
Order By: Relevance
“…Previous work had suggested that an instability was needed for spot onset. 16 The model presented here suggests a significantly different picture that does not include instability as a feature of spot onset.…”
Section: Introductionmentioning
confidence: 75%
See 1 more Smart Citation
“…Previous work had suggested that an instability was needed for spot onset. 16 The model presented here suggests a significantly different picture that does not include instability as a feature of spot onset.…”
Section: Introductionmentioning
confidence: 75%
“…Thus, quasineutrality must first be established on the high potential side, creating a region with E ≈ 0, before an imbalance in the static Langmuir condition implies expansion of the double layer. Previous attempts to model spot onset solved an integral form of Poisson's equation 16,28,29 . In these models, the integral of the charge density within the sheath, including contributions from electron impact ionization, were formulated as a function of the sheath electric field…”
Section: A Anode Spot Onsetmentioning
confidence: 99%
“…Actually, Knight theory does not deal with the reaction of the plasma on the electric field. Experimental [6] and theoretical [7,8,9,10] works showed that when an electric potential drop appears in a plasma, it tends to concentrate over a region of small extent (a few Debye lengths). It forms a coherent electrostatic structure, called double layer (DL) which is said to be strong when the potential drop exceeds the plasma thermal energy, and weak otherwise.…”
Section: Time Independent J : Quasi-static Acceleration Regionmentioning
confidence: 99%
“…In the present paper we report our investigations of the properties of EIC waves associated with a strong (eck/kTe 5-15), three-dimensional, magnetized double layer. The double layers are of the "anode type" as described by Torv•n and Andersson [1979] and Andersson [1981] in which a low rate of volume ionization provides the trapped electron species required to maintain the potential structures. These potential structures are produced in the diverging magnetic field region of a cylindrical argon discharge device, thus giving rise to V-shaped equipotentials.…”
mentioning
confidence: 99%